RF CMOS-MEMS cantilever resonator - Zainuddin, Ahmad Anwar; Karim, Jamilah; Nordin, Anis Nurashikin; Taufik, Mohamad Syamsi; Pandian, Mohanraj; Khan, Sheroz (2013)
This paper presents use of the simple cantilever beam as RF CMOS-MEMS resonator, which can be scaled like transistor with improved performance. This resonator can be used in the oscillator and filter part of RF transceiver, which can actually be fabricated on chip without losing its Q-factor. The cantilever beam resonator was designed using COMSOL4.3b™ and produce resonance frequency at 10.2MHz, pull-in voltage at 1.5V and Q of 10000.